Suture Choice in Lumbar Dural Closure Contributes to Variation in Leak Pressures: Experimental Model. Issue 6 (July 2017) - Ghobrial, George M.; Maulucci, Christopher M.; Viereck, Matthew J.; Beygi, Sara; Chitale, Ameet; Prasad, Srinivas; Jallo, Jack; Heller, Joshua; Sharan, Ashwini D.; Harrop, James S.
Abstract : Study Design: Open-label laboratory investigational study; non-animal surgical simulation. Objective: The authors perform a comparison of dural closure strength in a durotomy simulator across 2 different suture materials. Summary of Background Data: Incidental durotomy leading to persistent cerebrospinal fluid leak adds considerable morbidity to spinal procedures, often complicating routine elective lumbar spinal procedures. Using an experimental durotomy simulation, the authors compare the strength of closure using Gore-Tex with other suture types and sizes, using various closure techniques. Methods: A comparison of dural closures was performed through an analysis of the peak pressure at which leakage occurred from a standardized durotomy closure in an established cerebrospinal fluid repair model with a premade L3 laminectomy. Nurolon was compared with Gore-Tex sutures sizes (for Gore-Tex, CV-6/5-0 and CV-5/4-0 was compared with Nurolon 4-0, 5-0, and 6-0). Results: Thirty-six trials were performed with Nurolon 4-0, 5-0, and 6-0, whereas 21 trials were performed for 4-0 and 5-0 Gore-Tex. The mean peak pressure at which fluid leakage was observed was 21 cm H2 O for Nurolon and 34 cm H2 O for Gore-Tex. Irrespective of suture choice, all trials were grouped by closure technique: running suture, locked continuous, and interrupted suture. No significant difference was noted between the groups. For each of the 3 trials groups by closure technique, running, locked continuous, and interrupted, Gore-Tex closures had a significantly higher peak pressure to failure. Interrupted Gore-Tex was significantly higher than Interrupted Nurolon ( P =0.007), running Gore-Tex was significantly higher than running Nurolon ( P =0.034), and locked Gore-Tex was significantly higher than locked Nurolon ( P =0.014). Conclusions: Durotomy closure in the lumbar spine with Gore-Tex suture may be a reasonable option for providing a watertight closure. In this laboratory study, Gore-Tex suture provided watertight dural closures that withstood higher peak pressures.